2017
DOI: 10.1016/j.ultrasmedbio.2017.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Thrombolysis Using Microtripsy in a Porcine Deep Vein Thrombosis Model

Abstract: Histotripsy is a noninvasive therapeutic technique that uses ultrasound generated from outside the body to create controlled cavitation in targeted tissue, and fractionates it into acellular debris. We have developed a new histotripsy approach, termed microtripsy, to improve targeting accuracy and to avoid collateral tissue damage. This in vivo study evaluates the safety and efficacy of microtripsy for noninvasive thrombolysis in a porcine deep vein thrombosis (DVT) model. Acute thrombi were formed in left fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 41 publications
(54 reference statements)
4
31
0
Order By: Relevance
“…This technique applied to a tissue is called histotripsy, and when applied to thrombus is called thrombotripsy. This approach was investigated ex vivo 11‐17 and in vivo in a porcine model 18,19 , and achieved convincing results, but also highlighted important limitations such as potential damage to the vessel walls. Several improvements have been studied to better target the thrombus: microtripsy 12 was based on focusing high‐pressure pulses, and the approach developed by our team, 20 which relied on high frequency to achieve smaller focal zones and obtain better preserved vessel walls.…”
Section: Introductionmentioning
confidence: 99%
“…This technique applied to a tissue is called histotripsy, and when applied to thrombus is called thrombotripsy. This approach was investigated ex vivo 11‐17 and in vivo in a porcine model 18,19 , and achieved convincing results, but also highlighted important limitations such as potential damage to the vessel walls. Several improvements have been studied to better target the thrombus: microtripsy 12 was based on focusing high‐pressure pulses, and the approach developed by our team, 20 which relied on high frequency to achieve smaller focal zones and obtain better preserved vessel walls.…”
Section: Introductionmentioning
confidence: 99%
“…Histotripsy is a non-thermal ablation method which has been successful in tissue destruction via induced cavitation, and recently it has been applied for sonothrombolysis. One attractive feature of histotripsy is the ability to fractionate clots without the need of thrombolytic agent, thus eliminating the associated risks of thrombolytic treatments [38][39][40][111][112][113][114]. Early histotripsy studies demonstrated that this technique was effective for destroying clots and that the resulting clot debris can be minimized by adjusting the peak negative pressure, duty cycle, and pulse repetition frequency of the pulses [39,40,111].…”
Section: Therapeutic Ultrasoundmentioning
confidence: 99%
“…However, while clot debris sizes were primarily limited to less than 100 µm, initial in vivo animal studies demonstrated some vessel damage and hemorrhage in the region of excitation [111]. To address this, researchers developed a technique termed microtripsy, which allows the benefits of histotripsy while benefiting from a much smaller focal region, thus minimizing the risk for vasculature damage [38,112,113]. In in vivo animal studies, while some vessel damage and hemorrhage were observed, there was no damage observed in two weeks follow-up, indicating that this technique may improve the previous histotripsy technique [113].…”
Section: Therapeutic Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, histotripsy has the potential to be utilized in disease pathologies that would otherwise require surgical intervention Duryea et al 2011;Hall et al 2007b;Hempel et al 2011;Khokhlova et al 2014;Kim et al 2013Kim et al , 2014aMaxwell et al 2011a;Owens et al 2010;Schade et al 2015;Styn et al 2010;Vlaisavljevich et al 2013bVlaisavljevich et al , 2016cZhang et al 2017). Pre-clinical studies have investigated histotripsy for the treatment of thrombus obstruction (Bader et al 2016a;Maxwell et al 2011a;Sukovich et al 2017;Zhang et al 2017), fetal septal defects (Xu et al 2010), kidney stones (Duryea et al 2014), hepatocellular carcinoma (Khokhlova et al 2014;Vlaisavljevich et al 2013cVlaisavljevich et al , 2017b, renal carcinoma (Roberts et al 2006), transcranial ablation (Sukovich et al 2016) and biofilms (Bigelow et al 2018), amongst others (Khokhlova et al 2015). Furthermore, a clinical trial was recently completed whose primary outcome was to assess the safety of histotripsy technology to treat benign prostatic hyperplasia (Schuster et al 2018).…”
Section: Introductionmentioning
confidence: 99%